Macrophage activation syndrome in COVID-19 - K. N. Grigorieva; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; D. V. Blinov; V. I. Tsibizova; D. A. Ponomarev; A. S. Shkoda; E. A. Orudzhova; E. Grandone; G. Rizzo; A. D. Makatsariya (Акушерство, гинекология и репродукция)
The novel coronavirus epidemic is characterized by high rates of morbidity and relatively high mortality. Laboratory test results in patients include leukopenia, an increase in liver function tests and ferritin levels reaching hundreds, and sometimes thousands of units. These data remind us about the macrophage activation syndrome (MAC). Secondary hemophagocytic lymphohistiocytosis syndrome, MAC, which pathogenesis is based on a defect in the mechanisms of T-cell cytotoxicity and decreased level of natural killer cells associated with the defect in the perforin-encoding gene as well as hyperproduction of a number of cytokines – interleukin (IL)-1â, tumor necrosis factor-á, etc. by T-lymphocytes and histiocytes, indirectly leading to the activation of macrophages and production of proinflammatory cytokines, in particular IL-6 hyperproduction. MAC is one of "hyperferritinemic syndromes". These disorders have similar clinical and laboratory manifestations, and they also respond to similar treatments, suggesting that hyperferritinemia may be involved in the overall pathogenesis and is characterized by elevated ferritin level and cytokine storm. Despite the fact that data on the immune and inflammatory status in patients with COVID-19 have only started to appear, it is already clear that hyperinflammation and coagulopathy affect the disease severity and increase the risk of death in patients infected with SARS-CoV-2. Hence, understanding the pathogenesis of the novel coronavirus infection can help in its early diagnostics and treatment.